Identification of Formalin in Raw Tofu from Sidenreng Rappang District Traditional Markets - Hasrianti, Hasrianti; Suhaenah, Asriani; Pratama, Mamat (Universitas Muslim Indonesia, 2024)
Formalin (Formaldehyde) is a chemical compound whose use is prohibited as a preservative in food additives. This study aims to analyze the content of formalin (Formaldehyde) in raw tofu circulating in Sidenreng Rappang district. The test method used was by qualitative analysis using Schiff reagent and KMnO4. The quantitative analysis using the UV-Vis spectrophotometry method. The test results used Schiff reagent and KMnO4, the four tofu samples contained formalin. Test results on the UV-Vis Spectrophotometry method at a wavelength of 555 nm, obtained formalin levels in sample with sample code A = 1.130%, sample code B = 1.826%, sample code C = 1.84%. It can be concluded that in the formaldehyde qualitative analysis test on raw tofu, the three samples positively contained formaldehyde. As well as the results of the measurement of the three positive samples containing formaldehyde using a UV-Vis spectrophotometer.